A Cross-Cultural Examination of Hate Speech Targeting Transgender Celebrities Across Indonesian and International Social Media Platform - Hara, Nina Tiya; Siregar, Maysarah; Br. Perangin-angin, Alemina; Anshary, Elvira Putri (LingPoet: Journal of Linguistics and Literary Research, 2024)
This research investigates the pervasive phenomenon of online hate speech targeting transgender celebrities across Indonesian and International social media platforms. Focusing on experiences of Lucinta Luna and Caitlyn Jenner, the study aims to bridge a critical gap in understanding how cultural contexts shape the prevalence and nature of online harassment directed at transgender public figures. Through a comparative analysis, this research employs a mixed-theory approach that integrates Mondal's (2017) categorization of hate speech types and Kreidler's (2002) framework of hate speech intentions. The findings reveal that both Luna and Jenner share common experiences of online hate speech, with significant occurrences related to their behaviour, physical appearance, and gender identity. Notably, there was an absence of hate speech targeting disability, ethnicity, or race. Furthermore, the study uncovers that the major intentions behind the hate speech took the form of insulting and insinuating rhetoric. By exploring the unique challenges faced by Lucinta Luna and Caitlyn Jenner in navigating online spaces and addressing instances of hate speech, this research seeks to contribute to a deeper understanding of the complexities surrounding transgender celebrityhood and online harassment